Micro-Level Welfare Impacts of Agricultural Productivity: Evidence from Rural Malawi. Issue 5 (4th May 2018) - Darko, Francis Addeah; Palacios-Lopez, Amparo; Kilic, Talip; Ricker-Gilbert, Jacob
Abstract: This article analyses the micro-level welfare impacts of agricultural productivity using a two-wave nationally representative, panel data from rural Malawi. Welfare is measured by various dimensions of poverty and food insecurity; and agricultural productivity is measured by maize yield and value of crop output per hectare. The poverty measures included per capita consumption expenditure, relative deprivation in terms of per capita consumption expenditure, poverty gap and severity of poverty; and the measures of food insecurity included caloric intake and relative deprivation in terms of caloric intake. Depending on the measure of welfare, the impact of agricultural productivity was estimated with a household fixed effects estimator, a two-part estimator or a correlated-random effect ordered probit estimator. The results indicate that growth in agricultural productivity has the expected welfare-improving effect. In terms of economic magnitude, however, both the direct effect and economy-wide spillover effect (in the non-farm sector) of a percentage increase in agricultural productivity on the poverty and food security measures are small. Efforts to effectively improve the welfare of rural agricultural households should therefore go beyond merely increasing agricultural (land) productivity.